2018
DOI: 10.1038/s41467-018-06922-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into cGAMP degradation by Ecto-nucleotide pyrophosphatase phosphodiesterase 1

Abstract: ENPP1 (Ecto-nucleotide pyrophosphatase phosphodiesterase 1), a type II transmembrane glycoprotein, hydrolyzes ATP to produce AMP and diphosphate, thereby inhibiting bone mineralization. A recent study showed that ENPP1 also preferentially hydrolyzes 2′3′-cGAMP (cyclic GMP-AMP) but not its linkage isomer 3′3′-cGAMP, and negatively regulates the cGAS-STING pathway in the innate immune system. Here, we present the high-resolution crystal structures of ENPP1 in complex with 3′3′-cGAMP and the reaction intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 33 publications
3
109
0
Order By: Relevance
“…The nucleoside monophosphates AMP and GMP, the major ENPP-1 hydrolysis products of 2'3'-cGAMP, slightly inhibited [ 32 P] 2'3'-cGAMP uptake ( Fig. 4d) 24 consistent with previous observations that AMP, other nucleotides, and organic phosphates in general, inhibit SLC19A1-mediated transport 17,18 . Our findings indicated that SLC19A1 broadly interacts with CDNs irrespective of the phosphodiester linkages or the base content but that CDN breakdown products have a limited effect on CDN uptake.…”
supporting
confidence: 91%
“…The nucleoside monophosphates AMP and GMP, the major ENPP-1 hydrolysis products of 2'3'-cGAMP, slightly inhibited [ 32 P] 2'3'-cGAMP uptake ( Fig. 4d) 24 consistent with previous observations that AMP, other nucleotides, and organic phosphates in general, inhibit SLC19A1-mediated transport 17,18 . Our findings indicated that SLC19A1 broadly interacts with CDNs irrespective of the phosphodiester linkages or the base content but that CDN breakdown products have a limited effect on CDN uptake.…”
supporting
confidence: 91%
“…Overall, the human ENPP1 structures presented are similar to those of the secreted mouse ENPP1 (see Fig. 1; Kato et al, 2012Kato et al, , 2018Jansen et al, 2012). A high sequence identity (79.7%), particularly for the catalytic domain (88.4%), allowed the structure of the mouse enzyme, PDB entry 4b56, to be used to obtain the phases via molecular replacement.…”
Section: Resultsmentioning
confidence: 64%
“…Interestingly, a recent study shows that Ecto-nucleotide pyrophosphatase phosphodiesterase 1 (ENPP1), preferentially hydrolyzes 2′3′-cGAMP, but not 3′3′-cGAMP, thereby negatively regulates the cGAS-STING pathway (Wang et al, 2018a). This preferential degradation is due to its binding to the ENPP1 active site in a conformation suitable for catalysis (Kato et al, 2018). Thus, it needs to be further clarified if Compound C can affect cGAMP degradation by modulating ENPP1 activities.…”
Section: Discussionmentioning
confidence: 99%